Advancing destination image: The destination content model. (November 2016) - Kock, Florian; Josiassen, Alexander; Assaf, A. George
Highlights: Existing studies on destination image are integrated into a three-component model. Conceptual and empirical validation of an affective destination construct. The three components reliably and independently predict tourist behavior. Abstract: Knowledge of the mental representations that individuals hold about tourist destinations are important to understand their intentions. These mental destination representations have often been investigated by applying the concept of destination image. This study argues that the extant literature is often rather atheoretical and lacks operational rigor. These are major shortcomings which undoubtedly hinder the development of academic and managerial insights. In response, this study draws on contemporary psychology to develop the destination content model, comprising three informational components held in individuals' minds about destinations. The present study further outlines preferable methods and measures for each component, thus aiding researchers to investigate mental destination representations.